Oral Administration of Gintonin Protects the Brains of Mice against Aβ-Induced Alzheimer Disease Pathology: Antioxidant and Anti-Inflammatory Effects. (17th April 2021) - Ikram, Muhammad; Jo, Min Gi; Park, Tae Ju; Kim, Min Woo; Khan, Ibrahim; Jo, Myeung Hoon; Kim, Myeong Ok
Abstract : The study was aimed at analyzing the protective effects of gintonin in an amyloid beta- (A β -) induced Alzheimer's disease (AD) mouse model. For the development of the A β -induced AD mouse model, the amyloid- β (A β 1-42 ) peptide was stereotaxically injected into the brains of mice. Subsequently, gintonin was administered at a dose of 100 mg/kg/day/per oral (p.o) for four weeks daily, and its effects were evaluated by using western blotting, fluorescence analysis of brain sections, biochemical tests, and memory-related behavioral evaluations. To elucidate the effects of gintonin at the mechanistic level, the activation of endogenous antioxidant mechanisms, as well as the activation of astrocytes, microglia, and proinflammatory mediators such as nuclear factor erythroid 2-related factor 2 (NRF-2) and heme oxygenase-1 (HO-1), was evaluated. In addition, microglial cells (BV-2 cells) were used to analyze the effects of gintonin on microglial activation and signaling mechanisms. Collectively, the results suggested that gintonin reduced elevated oxidative stress by improving the expression of NRF-2 and HO-1 and thereby reducing the generation of reactive oxygen species (ROS) and lipid peroxidation (LPO). Moreover, gintonin significantly suppressed activated microglial cells and inflammatory mediators in the brains of A β -injected mice. Our findings also indicated improved synaptic and memory functions in the brains of A β -injected mice after treatment with gintonin. These results suggest that gintonin may be effective for relieving AD symptoms by regulating oxidative stress and inflammatory processes in a mouse model of AD. Collectively, the findings of this preclinical study highlight and endorse the potential, multitargeted protective effects of gintonin against AD-associated oxidative damage, neuroinflammation, cognitive impairment, and neurodegeneration.